2021
DOI: 10.18632/aging.203652
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the function and mechanism of m6A reader IGF2BP2 in Alzheimer’s disease

Abstract: Alzheimer’s disease, the most common form of dementia in the elderly, is a kind of neurodegenerative disease. However, its pathogenesis and diagnosis remain unclear. M6A is related to nervous system development and neurodegenerative diseases. Here in this study, using multiple RNA-seq datasets of Alzheimer’s brain tissues, along with bioinformatic analysis, we innovatively found that m6A reader protein IGF2BP2 was abnormally highly expressed in Alzheimer’s patients. After compared between Alzheimer’s and norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…The study of Wang et al showed that IGF2BP2 up-regulated the expression of circ 0000745 through microRNA-3187-3p/ErbB4/PI3K/Akt axis and promoted the aggressiveness and stemness of ovarian cancer cells [ 37 ]. Deng et al confirmed that IGF2PB2 can specifically bind to TP53I11, PKP2, BMP6, CFH and COL1A1 , through ECM–receptor interaction, cytokine–cytokine receptor interaction, and TGF-β signaling pathway in Alz play an important regulatory role in Haimer’s disease [ 38 ]. Other research indicates that IGF2BP2 plays a regulatory role in the pathological mechanisms of Lung ischemia–reperfusion injury (LIRI), Hemoglobin H-Constant Spring disease (HbH-CS), Autoimmune inflammation, and other diseases [ 39–41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Wang et al showed that IGF2BP2 up-regulated the expression of circ 0000745 through microRNA-3187-3p/ErbB4/PI3K/Akt axis and promoted the aggressiveness and stemness of ovarian cancer cells [ 37 ]. Deng et al confirmed that IGF2PB2 can specifically bind to TP53I11, PKP2, BMP6, CFH and COL1A1 , through ECM–receptor interaction, cytokine–cytokine receptor interaction, and TGF-β signaling pathway in Alz play an important regulatory role in Haimer’s disease [ 38 ]. Other research indicates that IGF2BP2 plays a regulatory role in the pathological mechanisms of Lung ischemia–reperfusion injury (LIRI), Hemoglobin H-Constant Spring disease (HbH-CS), Autoimmune inflammation, and other diseases [ 39–41 ].…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A modification have been reported to be involved in regulating the proliferation, differentiation, and apoptosis of bone-related cells including bone marrow mesenchymal stem cells, osteoblasts, and osteoclasts by multiple studies ( Huang et al, 2021 ) ( Wang et al, 2021b ; Chen et al, 2022 ) ( Wu et al, 2020 ). In addition, IGF2BP2 highly expressed in Alzheimer’s patients by bioinformatic analysis using multiple RNA-seq datasets of Alzheimer’s brain tissues ( Deng et al, 2021 ). Su et al found that age difference impacted m 6 A RNA methylation in hearts and their response to acute myocardial ischemia/reperfusion (I/R) injury ( Su et al, 2021 ).…”
Section: M 6 a Methylation Modification In Female ...mentioning
confidence: 99%
“…To date, increasing research have reported the connection between m 6 A and organ aging/cell senescence. However, most of them mainly focused on methyltransferase, such as METTL3/METTL14 ( Zhang J. et al, 2020 ; Wu et al, 2020 ; Liu et al, 2021 ; Chen et al, 2022 ), and the demethylases and readers were gradually concerned in recent years, including ALKBH5 ( Li et al, 2022a ), WTAP ( Li et al, 2022b ), IGF2BP2 ( Deng et al, 2021 ). Notedly, in reproductive aging, FTO has been shown to play the regulatory role ( Ding et al, 2018 ; Zhou L. et al, 2021 ; Jiang et al, 2021 ; Sun et al, 2021 ).…”
Section: M 6 a Methylation Modification In Female ...mentioning
confidence: 99%
“…Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases characterized by cognitive loss, which is mainly manifested as progressive memory dysfunction, cognitive dysfunction, personality abnormalities and language impairment [ 1 ]. AD is a disease that typically increases in incidence with age, with an incidence of less than 1% in the 60–64 age group, and the incidence increases exponentially with age.…”
Section: Introductionmentioning
confidence: 99%